#TITLE_ALTERNATIVE# - NUGROHO DWIE BASKORO (NIM : 13707058); Pembimbing Utama : Dr. Ir. Aditianto Ramelan, GURIT
Cement is one of materials used for civil construction and its mechanical properties increases with hydration time. However, certain cement has shown high variability on its compression strength. To understand this peculiar behaviour, observation need to be undertaken and at the same time specific characterisation method is requirred to relate compound formed in hydration process with compressive strength. The observation was made of 2 mixtures of cement pasta consist of water and 2 makes of pure cement (A and B) in order to reduce complexity of the analysis. The mixture were left hydrated for 3, 14 and 28 days with water-cement ratio (w/c) 0.3, 0.4 and 0.5. The compressive strength of both cement pasta were then compared and the compounds or phases formed were characterized by using x-ray diffraction. These experiments referred to ASTM C31 standard. It is observed that average compression strength of cement A at 3 days (w/c=0.3) is 40.47 MPa while cement B is 9.47 MPa. At the age of 28 days, cement A reached 43.62 MPa while B is 45.95 Mpa. XRD result at aged 3 days (w/c=0.3) shows calcite content in cement A (35.6 w/o) and B (51 w/o) as well as calcium silicate hydrate in cement A (32.2 w/o) and B (17.3 w/o). At the age of 28 days, almost no difference between their compounds formed. The differences in compressive strength at 3 days is due to the influence of inhomogenous mixing process. The phases determined for the cement A and B mixtures by using x-ray diffraction were able to show an association between hydration compounds formed and their mechanical properties. Further reasearches need to be carried out in future to find an accurate method for characterising hydrated cement products.